Cysticercosis of the Central Nervous System - How Should It Be Managed? - Garcia, Hector H. (2011)
PURPOSE OF REVIEW: Taenia solium neurocysticercosis has been long recognized as an important cause of neurological morbidity in most of the world. Unwarranted generalization of diagnostic and treatment recommendations made it difficult to assess individual prognosis and responses for each type of NCC. Understanding of the main clinical presentations (dependent on number, location, size and stage of parasites, as well as on the immune response of the host) allows a better view of treatment options and expected outcomes. RECENT FINDINGS: Current treatment options are still limited and involve symptomatic agents, antiparasitic agents or surgery. The importance of adequate symptomatic management, the potential for improved antiparasitic treatment regimes, in particular combination therapy, and the increasingly important role of minimally invasive neurosurgery are also revised in this manuscript. SUMMARY: Treatment decisions in NCC should be individualized in relation to the type of NCC. Initial measures should focus on symptomatic management to later consider antiparasitic therapy when appropriate. Appropiate patient categorization, new antiparasitic regimes and minimally invasive surgery are improving the prognosis of patients with NCC.